Motivating and preparing African youth for successful careers in agribusiness: Insights from agricultural role models. Issue 2 (16th November 2015) - Haggblade, Steven; Chapoto, Antony; Drame-Yayé, Aissetou; Hendriks, Sheryl L.; Kabwe, Stephen; Minde, Isaac; Mugisha, Johnny; Terblanche, Stephanus
Abstract : Purpose: – The purpose of this paper is to examine the career trajectories of 66 distinguished African agricultural professionals in order to explore how agricultural education and training (AET) institutions can better motivate and prepare youth for productive careers in Africa's rapidly changing agrifood system. Design/methodology/approach: – Based on in-depth qualitative interviews with these role models, the paper explores the answers to two critical questions: How can Africa motivate its youth to consider careers in agriculture and agribusiness? How can AET institutions better prepare youth for productive careers in agribusiness? Findings: – Rural youth enter agribusiness careers in response to clearly perceived rural needs coupled with demonstrable profitability of modern agricultural and agribusiness opportunities. In contrast, urban youth embark on agricultural career paths in response to inspiring science education, particularly practical applications in biology, coupled with emerging awareness of the range of professional opportunities afforded by modern agribusiness and commercial agriculture. Research limitations/implications: – The study relies on the basic premise that seasoned, successful professionals – from the private and public sector – can offer useful insights into ways of improving job preparation training for the youth of today seeking careers in the food system of tomorrow. The approach assumes that the role models have both the practical experience and forward-looking vision necessary to identify key elements of preparation likely to benefit future job market entrants. Originality/value: – This paper relies on primary interviews with distinguished agricultural professionals from 14 different African countries.